Leukaemia mortality in relation to magnetic field exposure: findings from a study of United Kingdom electricity generation and transmission workers, 1973–97. Issue 5 (1st May 2001) - Harrington, J M; Nichols, L; Sorahan, T; van Tongeren, M
Abstract : OBJECTIVE: To investigate whether risks of leukaemia are related to occupational exposure to magnetic fields. METHODS: The mortality experienced by a cohort of 83 997 employees of the former Central Electricity Generating Board of England and Wales was investigated for the period 1973–97. All employees were employed for at least 6 months with some employment in the period 1973–82. Computerised work histories were available for 79 972 study subjects for the period 1971–93. Detailed calculations were performed by others to enable a novel assessment to be made of exposures to magnetic fields. Two analytical approaches were used, indirect standardisation (n=83 997) and Poisson regression (n=79 972). RESULTS: Based on serial mortalities for England and Wales, the standardised mortality ratio of 84 for all leukaemias (observed 111, expected 132.3) was similar to that of 83 for all causes (observed 14 845, expected 17 918). No significant positive trends were found for the risks of various types of leukaemia (chronic lymphatic leukaemia, acute myeloid leukaemia, chronic myeloid leukaemia, all leukaemia) either with lifetime cumulative exposure to magnetic fields or with such exposures received in the most recent 5 years. CONCLUSIONS: There are no discernible excess risks of leukaemia as a consequence of occupational exposure to magnetic fields in United Kingdom electricity generation and transmission workers.